Small Engines as Bottoming Cycle Steam Expanders for Internal Combustion Engines - Rohitha Weerasinghe; Sandra Hounsham (Journal of Combustion)
Heat recovery bottoming cycles for internal combustion engines have opened new avenues for research into small steam expanders (Stobart and Weerasinghe, 2006). Dependable data for small steam expanders will allow us to predict their suitability as bottoming cycle engines and the fuel economy achieved by using them as bottoming cycles. Present paper is based on results of experiments carried out on small scale Wankel and two-stroke reciprocating engines as air expanders and as steam expanders. A test facility developed at Sussex used for measurements is comprised of a torque, power and speed measurements, electronic actuation of valves, synchronized data acquisition of pressure, and temperatures of steam and inside of the engines for steam and internal combustion cycles. Results are presented for four engine modes, namely, reciprocating engine in uniflow steam expansion mode and air expansion mode and rotary Wankel engine in steam expansion mode and air expansion mode. The air tests will provide base data for friction and motoring effects whereas steam tests will tell how effective the engines will be in this mode. Results for power, torque, and p-V diagrams are compared to determine the change in performance from air expansion mode to steam expansion mode.